Dental clinic management system - Hassan, Ahmad (2019)
DCMS is a web-based system that will help an organization of dental clinic to manage their operation systematically. Instead of using manual or traditional way to register new patient. Probability to lost the record of patients’ health is higher rather than using a system. The system will save the patients’ health record in database. Patient easily can book for an appointment.